CHL1 depletion affects dopamine receptor D2-dependent modulation of mouse behavior - Fernandes, Luciana; Kleene, Ralf; Congiu, Ludovica; Freitag, Sandra; Kneussel, Matthias; Loers, Gabriele; Schachner, Melitta (Frontiers in Behavioral Neuroscience, 2023)
The dopaminergic system plays a key role in the appropriate functioning of the central nervous system, where it is essential for emotional balance, arousal, reward, and motor control. The cell adhesion molecule close homolog of L1 (CHL1) contributes to dopaminergic system development, and CHL1 and the dopamine receptor D2 (D2R) are associated with mental disorders like schizophrenia, addiction, autism spectrum disorder and depression. Here, we investigated how the interplay between CHL1 and D2R affects the behavior of young adult male and female wild-type (CHL+/+) and CHL1-deficient (CHL1−/−) mice, when D2R agonist quinpirole and antagonist sulpiride are applied. Low doses of quinpirole (0.02 mg/kg body weight) induced hypolocomotion of CHL1+/+ and CHL1−/− males and females, but led to a delayed response in CHL1−/− mice. Sulpiride (1 mg/kg body weight) affected locomotion of CHL1−/− females and social interaction of CHL1+/+ females as well as social interactions of CHL1−/− and CHL1+/+ males. Quinpirole increased novelty-seeking behavior of CHL1−/− males compared to CHL1+/+ males. Vehicle-treated CHL1−/− males and females showed enhanced working memory and reduced stress-related behavior. We propose that CHL1 regulates D2R-dependent functions in vivo. Deficiency of CHL1 leads to abnormal locomotor activity, and emotionality and sex-dependent behavioral differences.